Pregunta
upstudy study bank question image url

\( 2.2 \quad \) Given: \( \sum_{p=k}^{10} 3^{p-1}=29520 \). Calculate the value of \( k \).

Ask by Crawford Welch. in South Africa
Feb 19,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The value of \( k \) is 3.

Solución

We are given the equation   ∑ from p = k to 10 of 3^(p – 1) = 29520. Step 1. Rewrite the sum in a more convenient form. Let i = p – 1, so when p = k, i = k – 1, and when p = 10, i = 9. Then the sum becomes   ∑ from i = k – 1 to 9 of 3^i. Step 2. Use the formula for the sum of a geometric series:   ∑ from i = m to n of r^i = (r^(n + 1) – r^m)/(r – 1). In our case, r = 3, m = k – 1, and n = 9. So   ∑ from i = k – 1 to 9 of 3^i = (3^(10) – 3^(k – 1))/(3 – 1) = (3^(10) – 3^(k – 1))/2. Step 3. Set the sum equal to 29520 and solve:   (3^(10) – 3^(k – 1))/2 = 29520. Multiply both sides by 2:   3^(10) – 3^(k – 1) = 59040. Step 4. Calculate 3^(10):   3^(10) = 59049. Substitute into the equation:   59049 – 3^(k – 1) = 59040. Subtract 59040 from 59049:   3^(k – 1) = 59049 – 59040 = 9. Since 9 = 3^2, we have:   3^(k – 1) = 3^2. Thus, equate the exponents:   k – 1 = 2  →  k = 3. The value of k is 3.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the equation \( \sum_{p=k}^{10} 3^{p-1} = 29520 \), we first rewrite the summation: \[ \sum_{p=k}^{10} 3^{p-1} = 3^{k-1} + 3^k + 3^{k+1} + \ldots + 3^{9} + 3^{10} \] This can be recognized as a geometric series. The first term of the series is \( 3^{k-1} \) and the last term is \( 3^{9} \). The number of terms in this series is \( 10 - k + 1 = 11 - k \). The sum of a geometric series can be calculated using the formula: \[ S_n = a \frac{r^n - 1}{r - 1} \] where \( a \) is the first term, \( r \) is the common ratio, and \( n \) is the number of terms. Here, \( a = 3^{k-1} \), \( r = 3 \), and \( n = 11 - k \). Thus, the sum becomes: \[ \sum_{p=k}^{10} 3^{p-1} = 3^{k-1} \frac{3^{11 - k} - 1}{3 - 1} = 3^{k-1} \frac{3^{11 - k} - 1}{2} \] Setting this equal to \( 29520 \): \[ 3^{k-1} \frac{3^{11 - k} - 1}{2} = 29520 \] Multiplying both sides by 2 gives: \[ 3^{k-1} (3^{11 - k} - 1) = 59040 \] Now, we can simplify \( 3^{k-1} (3^{11 - k} - 1) \): \[ 3^{k-1} (3^{11 - k} - 1) = 3^{10} - 3^{k-1} = 59040 \] Calculating \( 3^{10} \): \[ 3^{10} = 59049 \] Therefore, we can now rewrite the equation: \[ 59049 - 3^{k-1} = 59040 \] This leads us to: \[ 3^{k-1} = 59049 - 59040 = 9 \] Since \( 9 = 3^2 \): \[ k - 1 = 2 \quad \Rightarrow \quad k = 3 \] Thus, the value of \( k \) is \( \boxed{3} \).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad